PERCEPTION OF PHRA APHAI MANEE THROUGH PRINT MEDIA IN THAI SOCIETY - Khumsubdee, Sasinat; Udomsilp , Panupong (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This article aims to explore the perception of Phra Aphai Manee through print media in Thai society. The study compiled and analyzed the data from 47 printed works that feature narratives of Phra Aphai Manee, including poem story of Phra Aphai Manee written by Sunthorn Phu, Thai language textbooks, picture story books, comic adaptation books, and novels. The research employed textual analysis to examine the formats, presentation techniques, and important content of the Phra Aphai Manee story in each type of print media. The complete edition of the poem story of Phra Aphai Manee by written by Sunthorn Phu, published by Silpabannakarn Publishing, was used as the primary reference text. The findings revealed that public perception of Phra Aphai Manee through print media can be categorized into three main forms: 1) perception of Phra Aphai Manee through the plot structure, 2) perception of Phra Aphai Manee through key characters, and 3) perception of Phra Aphai Manee through significant events in the narrative. These three forms of perception highlight the core elements of the story that are widely recognized by Thai audiences. Furthermore, they reflect the objective of how the story is received through print media in Thai society, which can be grouped into three purposes: 1) perception aimed at preserving the original storyline, 2) perception tailored to the specific interests of target audiences, and 3) perception intended to preserve key elements of the tale. Overall, the study underscores the significance of Phra Aphai Manee as a major work of Thai literature that continues to be adapted, reproduced, and presented through modern media. Its sustained presence across various forms of media reflects the story’s cultural relevance and its dynamic role in Thai society across different generations.